Changes in Insulin Sensitivity and Lipid Profile Markers Following Initial and Secondary Bouts of Multiple Eccentric Exercises - Trevor C. Chen; Min-Jyue Huang; Leonardo C. R. Lima; Tai-Ying Chou; Tai-Ying Chou; Hung-Hao Wang; Jui-Hung Tu; Shi-Che Lin; Kazunori Nosaka (Frontiers in Physiology, 2022)
An acute bout of eccentric exercise affects insulin sensitivity and lipid profile, but how the magnitude of muscle damage affects them is not clear. We compared changes in blood insulin sensitivity and lipid markers after the first (EC1) and second (EC2) eccentric exercise bouts. Fifteen sedentary young men performed arm, leg and trunk muscle eccentric exercises, and repeated them 2 weeks later. Fasting blood samples were taken before, 2 h and 1–5 days after each exercise bout to analyze plasma creatine kinase (CK) activity, serum glucose (GLU), insulin, homeostasis model assessment (HOMA), triacylglycerols (TG), total (TC) and low- (LDLC) and high-density lipoprotein cholesterol (HDLC) concentrations as well as TC/HDLC ratio. Changes in these measures were compared between bouts and relationships to peak plasma CK activity were analyzed. Plasma CK activity increased (p < 0.05) after EC1 (peak: 101,668 ± 58,955 IU/L) but not after EC2. The magnitude of changes in GLU (peak after EC1: 26 ± 10% vs. EC2: 7 ± 6%), insulin (46 ± 27% vs. 15 ± 8%), HOMA (86 ± 48% vs. 24 ± 15%), TC (−20 ± 5% vs. −6 ± 4%), TG (−32 ± 11% vs. −6 ± 3%), LDHC (−47 ± 15% vs. −12 ± 9%), HDLC (35 ± 26% vs. 7 ± 4%), and TC/HDLC ratio (−139 ± 13% vs. −11 ± 7%) were significantly greater after EC1 than EC2. Peak plasma CK activity was significantly (p < 0.05) correlated with the peak changes in blood insulin sensitivity and lipid markers for the combined data of EC1 and EC2. These results suggest that the greater the magnitude of muscle damage, the greater the magnitude of changes in the insulin sensitivity to a negative direction and lipid markers to a positive direction.